La recuperación del uso de morteros de cal. La situación en el Perú - Barbero Barrera , María del Mar; Montoya Robles , Teresa del Pilar (Pontificia Universidad Católica del Perú, 2025)
Traditional materials have been part of our society across much of the world and, by extension, were also widely used in Peru up until the 20th century. The arrival of new materials such as cement and concrete has led to a sudden loss of the knowledge once held about traditional materials. However, in restoration and conservation processes of cultural buildings, understanding the characteristics and types of materials present in such structures is essential, both for their consolidation and reintegration. This requires not only the recovery of the material itself but, more importantly, the revival of traditional skills and the knowledge associated with them. Lime is no exception to this process and, unfortunately, the knowledge related to its use has also been lost. This article explores the use of lime as a traditional material and the importance of its recovery, not only due to its compatibility with traditional substrates but also because of its technical properties, which make it one of the most significant binding agents of both the past and the future.

Los materiales tradicionales han formado parte de las sociedades de buena parte del mundo y, por extensión, se utilizaron ampliamente en el Perú hasta el siglo XX. La llegada de nuevos materiales, tales como el cemento y el hormigón, ha generado una pérdida abrupta del conocimiento sobre los materiales tradicionales. Sin embargo, en procesos de restauración y conservación de edificios culturales es imprescindible conocer las características y los tipos de materiales presentes en dichas edificaciones, tanto para su consolidación como para su reintegración. Esto implica no solo la recuperación del material sino, sobre todo, la recuperación de los saberes tradicionales y de los conocimientos ligados a estos. La cal no es un material exento a este proceso y, lamentablemente, se ha perdido en gran medida el conocimiento ligado a su empleo. En este artículo se investiga el uso de la cal como material tradicional; asimismo, se estudia la importancia de su recuperación, no solo por la compatibilidad con los soportes tradicionales, sino también por sus prestaciones técnicas, que la convierten en uno de los conglomerantes más importantes del pasado y del futuro.
Recovery of Lime Mortar Use. The Situation in Peru
Keywords: Lime; Conservation; Restoration; Peru; Perception; Cal; Conservación; Restauración; Perú; Percepción; https://purl.org/pe-repo/ocde/ford#6.04.08